Messenger RNA Expression of Toll-Like Receptors 2, 4 and 9 in periodontitis - Chrzęszczyk, Dariusz; Baczyńska, Dagmara; Konopka, Tomasz (Journal of Stomatology, 2017)
Introduction. Many studies focus on significant differences in the expression of TLRs in periodontitis and healthy controls. The biological function of TLRs must have its toll on the host response to opportunistic bacteria present in the oral cavity and in the gingival sulcus/periodontal pocket. Aim of the study. To assess TLR2, TLR4 and TLR9 expression in periodontal tissues in patients with chronic and aggressive periodontitis. Also to compare studied TLRs’ expression with clinical parameters of periodontitis and evaluate clinical periodontal status among patients with very low and very high expression of examined TLRs. Material and methods. The study included 62 patients aged from 17 to 70 years with chronic (CP-34) and aggressive periodontitis (AgP-28) and 30 healthy controls. From all participants a fragment of the gingival tissue was taken to assess the expression of mRNA TLRs. Results. All patients had significantly higher expression of TLR4 and TLR9 compared to control. TLR9 expression was significantly higher in the CP with regard to AgP. There was no significant correlation between the expression of TLRs and clinical variables in all subjects with CP. Patients with AgP exhibited positive correlations between the expression of all TLRs and the presence of plaque. This group also showed positive correlations between the expression of TLR4 and TLR9 and the severity of periodontitis. Substantially higher values of all periodontal indices and a lower number of teeth were reported in 15 individuals with the highest expressions of TLR4. 15 patients with the highest expressions of TLR9 showed significantly higher rates only for plaque, severity and extent of inflammation indices. Conclusions. Regardless of the clinical diagnosis high TLR4 mRNA expression in the gingival tissue is associated with the severity, generalization and progression of periodontitis. High TLR9 expression is associated mainly with plaque, and could fulfill the protective function against progression of periodontitis.